Le Maroc dans l’affiche française (1906-1956) - Pascal Blanchard (Casa de Velázquez, 2007)
Between 1906 and 1956 Morocco became a place of inspiration for French poster artists, at the same time as it was drawn into the imperial structure of the Third Republic. This was evident as Morocco developed into one of the recurrent « themes » of poster production in the colonial context, in step with the absorption of the protectorate into the colonial geography of France; but it was a latecomer to this graphic universe, which explains its specific position and the relative uniformity of the output. We can identify three stages in this creative process, which cut across the broad lines of evolution of the poster in France: the time of discovery (1906-1926), the time of consolidation of a perspective (1926-1940) and the time of mutation of an image (1946-1956). It is a mythical Morocco that emerges in this art, with its own codes, its own imagery and its own specific goals under the guiding hand of the coloniser.